2019
DOI: 10.3390/horticulturae5010021
|View full text |Cite
|
Sign up to set email alerts
|

Use of Diatomaceous Earth as a Silica Supplement on Potted Ornamentals

Abstract: The role of silica as a needed supplement in soilless media is gaining interest. This research studied the effects of diatomaceous earth as a supplement on growth and flower characteristics, physiology, and nutrient uptake in dahlia (Dahlia Cav. × hybrida ‘Dahlinova Montana’), black-eyed Susan (Rudbeckia hirta L. ‘Denver Daisy’), and daisy (Gerbera jamesonii L. ‘Festival Light Eye White Shades’). Plants were either well-watered at 10 centibars or water-stressed at 20 centibars. Silicon treatments included top-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…2A and B) is probably due to the application of Si as ASF and the low Si content of the soil. Previous studies have confirmed the increased availability of Si in soils amended with amorphous silica-based fertilizers (Mills-Ibibofori et al 2019;Oliva et al 2020;Prakash et al 2016). Jeer et al (2020) found that the Si available in the soil increased between 33 and 44% after amending150 and 300 kg ha −1 of ASF to a clay loam soil.…”
Section: Discussionmentioning
confidence: 81%
“…2A and B) is probably due to the application of Si as ASF and the low Si content of the soil. Previous studies have confirmed the increased availability of Si in soils amended with amorphous silica-based fertilizers (Mills-Ibibofori et al 2019;Oliva et al 2020;Prakash et al 2016). Jeer et al (2020) found that the Si available in the soil increased between 33 and 44% after amending150 and 300 kg ha −1 of ASF to a clay loam soil.…”
Section: Discussionmentioning
confidence: 81%
“…Therefore, the resulting polysicilic polymer, the amorphous biosilica, SiO 2 xnH 2 O, is in a metastable state and rapidly releases silicic acid in an aqueous environment [73]. Due to this characteristic, DE-based products were used to provide soluble silicon species, i.e., silicic acid and its dimers and trimers, to the plants by treatment in the rhizosphere [74][75][76] and phyllosphere [77]. Zeolites also release soluble silicon species.…”
Section: Discussionmentioning
confidence: 99%
“…A commercial DE product (Perma-Guard, Inc., Kamas, UT, USA), used as a soluble silicon supplement to the growing medium, increased the tolerance to water stress of potted ornamentals-black-eyed Susan, Rudbeckia hirta, dahlia, Dahlia Cav. × hybrid, and daisy, Gerbera jamesonii [76].…”
Section: Discussionmentioning
confidence: 99%
“…Rice hulls have been used to supplement Si (Boldt et al 2018;Frantz et al 2010;Jayawardana et al 2016;Sistani et al 1997;Somapala et al 2016), but their release rate is not well-studied. Diatomaceous earth has been used for pest control, but is not well-studied as a Si supplement (Mills-Ibibofori et al 2019;Pati et al 2016). Wollastonite is a naturally occurring calcium silicate mineral (CaSiO 3 ) that is approximately 51% SiO 2 (Vanderbilt Minerals, LLC 2018) and has shown promise as an Si amendment (Haque et al 2019(Haque et al , 2020.…”
mentioning
confidence: 99%